Adaptation to Polycentricity. Relations Between Russia and Europe in a new Round of Interstate Rivalry - A. A. Gromyko; V. V. Sutyrin (Сравнительная политика, 2024)
The current cycle of interstate rivalry and crisis of European security raises the issues of civilizational identity of Russia and relations between the West and East of Europe. The analysis examines a broad range of political, historical and cultural problems that determine the modern place and role of Russia in Europe. The current features of interstate rivalry and its structure are revealed. An analysis of the causes and historical parallels of recent events, including those related to the escalation of the Ukrainian crisis, is given. The strategic risks and opportunities of Russian foreign policy in Europe are outlined. It is underlined that the increasing aggressiveness of Western policy is dictated by the crisis of the neoliberal model of globalization. The European space of the EU and NATO increasingly finds itself in a situation where its ability to play a dominant role in the world is decreasing and it becomes necessary to adapt to the conditions of a polycentric world order. The inability of the West to keep pace with event produces the search for an external enemy, and the growing mentality of a besieged fortress. The West increasingly imports external risks by pedalling the Ukrainian crisis as well as the dogmatic course towards expanding the EU and NATO at the expense of Ukraine and other post-Soviet countries. In the current circumstances, while making much-needed efforts to preserve and strengthen Russian identity, it is important not to leave the concept of Europe at the mercy of those who do not understand Russia or are hostile to it.